Evolution of changes in cognitive function after the initiation of antiretroviral therapy. - Mora-Peris,B; Stevens,E; Ferretti,F; Underwood,J; Taylor,S; Winston,A (AIDS Research and Therapy, 2016)
BACKGROUND: Cognitive function is reported to improve after the initiation of combination antiretroviral therapy (cART). Data on the evolution of such changes are limited. We assessed the dynamics of changes in cognitive parameters, in HIV-positive subjects initiating cART. METHODS: Cognitive function in seven domains was evaluated for HIV-infected patients without clinically significant cognitive impairment prior to the initiation of cART, and 24 and 48 weeks after. Cognitive scores were transformed using standardised z-scores according to the pooled baseline standard deviation. Global, speed, and accuracy composite z-scores were calculated with changes calculated using a paired t test. RESULTS: In 14 subjects, change in global cognitive z-scores from baseline was by 0.08 at week 24 (p = 0.59) and 0.15 at week 48 (p = 0.43). Change in composite speed and accuracy z-scores from baseline at weeks 24/48 were 0.07/0.05 (p = 0.45/0.82) and 0.13/0.23 (p = 0.47/0.45), respectively. In two of the cognitive domains assessing speed (learning and monitoring time), a continued improvement from baseline to weeks 24 and 48 was observed (changes of 0.06-0.08 and 0.10-0.19, respectively), whereas in two domains (detection and identification) an initial improvement at week 24 (changes of -0.10 and 0.04 from baseline, respectively) was followed by a deterioration in score at week 48 (changes of -0.12 and -0.08 from baseline, respectively). None of these changes were statistically significant. CONCLUSIONS: A trend for improvement in cognitive function was observed in naïve HIV-positive patients starting cART. The dynamics of this improvement differed both between cognitive domains and the time-points assessed.